"It takes three to tango": Brain, cognition and entrepreneurial enhancement - Víctor Pérez-Centeno (Institut für Mittelstandsforschung (IfM) Bonn, 2017)
In the global clash for unveiling the 'innermost secrets' of the brain, the field of neuroscience is the most fitting contender. Neuroscience is not quite ready to win the war for now, but it is assuredly equipped to win some battles. Notwithstanding that entrepreneurship is fundamentally a braindriven phenomenon, entrepreneurship research based on neuroscience's tools cannot be counted on the fingers of more than one hand. Grounded on a prior literature review that investigates the state of neuroscience's use in entrepreneurship research, this position paper reflects on the future implications that the utilization of neuroscience brings to entrepreneurship research and cognition. To articulate this exercise, I present the so-called five 'winds of disruption' to signal where to go next in the study of entrepreneurship from a brain-driven perspective. Next I spell out four ways to maximize neuroscience's inputs into entrepreneurship research. Furthermore, I synthesize the value of three neuroscience-based tools to rear and boost 'entrepreneurial enhancement', the ultimate challenge in the orbit of entrepreneurship research.
Additional information: Das vorliegende Positionspapier stellt Perspektiven und Herausforderungen der neurowissenschaftlichen Gründungsforschung vor.
Keywords: L26; M13; O33; 330; entrepreneurial neuroscience; neuro-entrepreneurship; entrepreneurial enhancement; cognition; brain-driven entrepreneurship; entrepreneurial enhancement